STRATEGI PENGEMBANGAN WISATA NDAYU PARK DALAM MENINGKATKAN DAYA TARIK WISATA DI KABUPATEK SRAGEN - Yuni Dwi Lestari; Kris Cahyani Ermawati; Sugiman Sugiman; Suharto Suharto (LPPM Politeknik Pajajaran ICB Bandung, 2025)
This study aims to determine the development strategies of Ndayu Park in enhancing the tourist appeal of Sragen Regency and the roles of stakeholders involved in the development process. The research questions are: (1) What are the development strategies of Ndayu Park as a tourist attraction? (2) What are the roles of stakeholders in the development of Ndayu Park as a tourist attraction? Research objectives: (1) To identify the development strategies for Ndayu Park. (2) To identify the role of stakeholders in the development of Ndayu Park. The research method used in this study is qualitative descriptive, employing data collection techniques such as observation, in-depth interviews, documentation, and literature review. The research findings indicate that Ndayu Park has significant potential as an educational and family tourist destination through the 4A strategy (Attraction, Accessibility, Amenities, Ancillary) and the concept of “Something to See, Something to Do, Something to Buy,” along with a SWOT analysis to outline the Strengths, Weaknesses, Opportunities, and Threats of Ndayu Park. This study recommends enhancing digital promotion, adding indoor attractions, and strengthening cross-sector collaboration to position Ndayu Park as a premier destination in Sragen Regency.